Cannabis use and sleep: Expectations, outcomes, and the role of age. (January 2021) - Winiger, Evan A.; Hitchcock, Leah N.; Bryan, Angela D.; Cinnamon Bidwell, L.
Highlights: Cannabis use associated with increased expectation that cannabis improves sleep. Limited support that cannabis is associated with sleep outcomes (PSQI). Currently using cannabis predicts decreased subjective sleep quality. Increased frequency of consuming edibles predicted worse subjective sleep efficiency, lower sleep duration, and higher global PSQI scores. Age likely moderates the effect of reported concentration of CBD on better sleep duration and efficiency. Abstract: Study Objectives: Determine relationship between cannabis use with 1) expectations of cannabis being a sleep aid, 2) subjective sleep outcomes, and 3) the influence of age on these relationships. Methods : In 152 moderate cannabis users with a wide age range (67% female, mean age = 31.45, SD = 12.96, age range = 21–70; mean days of cannabis use in prior two weeks = 5.54, SD = 5.25) we examined the influence of cannabis use history and behaviors on expectations of cannabis being a sleep aid and sleep outcomes via the Pittsburgh Sleep Quality Index (PSQI). Moderation analysis examined the role of age in the relationship between cannabis use and sleep outcomes. Results: Endorsing current cannabis use and more days of cannabis use were associated with increased expectations that cannabis use improves sleep (all β > 0.03, p  < 0.04). Frequency of recent use and reported average THC or CBD concentration were largely not associated with sleep outcomes. However, endorsing current cannabis use was associated with worse subjective sleep quality ( β  = 1.34, p  = 0.02) and increased frequency of consuming edibles was associated with worse subjective sleep efficiency (β = 0.03, p = 0.04), lower sleep duration (β = 0.03, p = 0.01), and higher global PSQI scores (worse overall sleep) ( β  = 0.10, p  = 0.01). Additionally, age had a moderating influence on the relationship between increased self-reported concentration of CBD and both better sleep duration and sleep quality (both p  < 0.03). While the main effects of cannabis use on sleep outcomes did not survive multiple comparisons correction test (all p adj > 0.34), the adjusted p values for the main effects of cannabis behaviors/history on expectations of cannabis as a sleep aid ( p adj = 0.07–0.09) and the main effects of CBD concentration on sleep duration ( p adj = 0.08), as well as the interaction terms of CBD and age for that model ( p adj = 0.07), were trending. Conclusion: Cannabis users have increased expectations of cannabis being a sleep aid, but few associations existed between cannabis use and sleep outcomes. The two exceptions were endorsing any cannabis use and frequency of edible use. Additionally, age may be an important moderator of the potential positive influence CBD concentration can have on sleep.